Synthesis and characterization of jatropha oil-based polyurethane acrylate polymer electrolyte - Tuan Naiwi, Tuan Syarifah Rossyidah (2017)
Solid polymer electrolyte has been extensively studied as an alternative to liquid electrolyte which is often affected by several issues including leakage, deformation and limited range of operating temperature. Bio-based polymer derived from vegetable oil has been proposed to substitute petroleum-based polymer due to its fluctuations in price, non-renewable resources and non-environmentally friendly. A non-edible jatropha oil (JO), processed from seeds of Jatrophacurcas,has received much attention due to its high-quality bio-fuel. The present study was conducted in an attempt to synthesize polyurethane acrylate (PUA) as host polymer from JO and to evaluate polymer performance supplemented with Li salt and plasticizers as polymer electrolytes. In the study, bio-based polyol was synthesized by epoxidation and ring opening reactions. Toluene 2, 4-diisocyanate (TDI) was added to polyol followed by hydroxylethylmethylacrylate (HEMA) to produce PUA. Hexanedioldiacrylate (HDDA) was used as a cross-linkable active diluent and Darocur 1173 (D-1173) was used as photoinitiator in UV curable PUA films. Lithium perchlorate (LiClO4) salt, varying from 5 wt% to 30 wt%, was used in PUA electrolyte to determine the optimum ionic conductivity. PUA with 25 wt% lithium salt recorded the highest conductivity of 6.4 x 10-5 Scm-1. The cation transference number achieved was 0.99, whereas the electrochemical stability exhibited 4.0 V. The spectroscopy analysis examined by Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) spectroscopy showed the interaction of lithium salts with oxygen and nitrogen atom in PUA polymer. The glass transition temperature of PUA electrolyte was lower than pristine PUA and they were negligible with increase in Li salt in the polymer electrolyte. The melting temperature of PUA electrolyte did not show significant trend with Li salt supplementation. The crystallinity and morphology studied showed that the polymer electrolyte was amorphous with the addition of salt which confirmed that the mixtures were homogeneous. The best of 25 wt% lithium salt was chosen to further study on the effect of plasticizers on the ratio of 3 wt% to 15 wt% ethylene carbonate (EC) in PUA electrolyte. The 9 wt% of EC showed the ionic conductivity had improved to 7.86 x10-4 Scm-1. The inclusion of plasticizers did not show any interaction changes in the polymer electrolyte by FTIR and NMR. The glass transition temperature and melting temperature decreased with the addition of plasticizers. Further examination on the crystallinity and morphology showed that the salt was not homogeneously distributed over polymer matrix when the polymer exhibited a semi-crystalline phase. Study on the electrochemical stability of polymer electrolyte widened to 4.0V. The bio-based polyurethane acrylate JO exhibited a high ionic conductivity and electrochemical stability that have potential applications for electrochemical devices. However, the incorporation of plasticizers did not show any significant improvement on thermal properties observed in the study.